Self-test and calibration methods for micro electro-mechanical systems - Anwer Sabah Ahmed; Qais Al-Gayem (Universitas Ahmad Dahlan, 2023)
For the testing of micro electro-mechanical systems, we propose a taxonomy of built-in self-testing methods. These solutions that are non-intrusive, cost-effective and are typically non-intrusive during the testing process are being actively sought after as the cost of micro-electro-mechanical systems (MEMS) testing can account for 50% of the total cost of the end product. The selection of testing methods is analyzed extensively, and a classification table for such methods is presented according to three performance metrics: ease of application, test application, usefulness. Performance table also provides a field test domain for the method. While built-in-self-test (BIST) methods do depend on the application at hand, utilizing the inherent multimodal sensing capability of most sensors could be a promising approach for effective built-in self-test.